The book of evidence - Achinstein, Peter (Oxford studies in philosophy of science., 2001)
What is required for something to be evidence for an hypothesis? In this text, Peter Achinstein, introduces here a basic concept of potential evidence which is characterised using a novel epistemic interpretation of probability.